(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The primary health care centers initiatives are designed to improve patient care and health outcomes. A process failed to address the impact on health outcomes, patient satisfaction, and costly of chronic diseases expected to adolescents. This study aimed to determine the role of quality of primary health care centers (PHCCs) on adolescents’ health status with chronic diseases in kirkuk city. Methodology: A descriptive (quantitative design ) was conducted through (18) PHCCs in Kirkuk city. Two questionnaires were designed for the purpose of the study. A simple random sample of (180) health professional (manager) were selected through the use of probability sampling approach. The sample of study was divided into two groups which include organization structure (PHC )centers (18) and (162) adolesents with chronic diseases. .Data analysis is performed through the use of descriptive statistical data analysis approach. Results: the overall evaluation for the quality of PHCCs is adequate on (59% ; N=11), and fair on (41% ; N=7) respectively. The quality of PHCCs is adequate relative to all of its dimensions of general health status, tangibles, accreditation, responsiveness, assurance and empathy. The experienced good level for the general, physical, mental, relationships and emotional dimensions of health status with chronic diseases Inadequate on Adequate on (44.%: n=71 ) ,Fair on (34.% :n= 55 ) ,and Inadequate (23. % :n=36 ) , level of evaluation . except that of the quality of life dimension of health status Adequate on Fair on (37.%: n = 60 ), Inadequate (n 30 %: =49 ),and Adequate (33.% n=53 ) does not impose any effect on adolescents’ general health status. Conclusion: The study findings depict that the quality of PHCCs is adequate relative to all of its dimensions of general health status, tangibles, accreditation, responsiveness, assurance, and empathy. Adolescents’ health status is good regardless of their age groups as being early, middle and late age adolescents except that of the quality of life dimension of health status which has a fair level of evaluation. The study confirms that the Impact of quality of PHCCs does not execute an impact on adolescents’ health status.